Procyanidin Improves Erectile Function in Rats by Inhibiting PDE5A Activity - Su Y; Shui J; Qi D; Bai J; Xu X; Huang Y; Li R; Wu Q; Wang H; Cao C; Su Z; Zhang S (Drug Design, Development and Therapy)
Yudong Su,1,2,* Jinman Shui,1,* Danshi Qi,1 Jie Bai,1 Xiaoxia Xu,2 Yongchun Huang,1 Ruilian Li,1 Qiong Wu,2 Haiyan Wang,2 Chengzhu Cao,2 Zhanhai Su,2 Shoude Zhang1,3 1School of Pharmacy, Qinghai University, Xining, Qinghai, People’s Republic of China; 2Department of Basic Medical Sciences, Qinghai University Medical College, Xining, Qinghai, People’s Republic of China; 3State Key Laboratory of Plateau Ecology and Agriculture, Qinghai University, Xining, Qinghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhanhai Su, School of Pharmacy, Qinghai University, Xining, Qinghai, People’s Republic of China, Email suzhanhai@qhu.edu.cn Shoude Zhang, School of Pharmacy, Qinghai University, Xining, Qinghai, People’s Republic of China, Email shoude.zhang@qhu.edu.cnPurpose: Erectile dysfunction (ED), a prevalent form of male sexual dysfunction, is predominantly treated with Phosphodiesterase type 5 inhibitors (PDE5Is). Our previous research highlighted procyanidin, a natural compound, as a notably effective PDE5I. In the current study, we intend to further validate the inhibitory activity of procyanidin on PDE5A through in vitro and in vivo assessments. This study aims to validate the efficacy of procyanidin as a treatment for ED.Methods: The binding affinity of procyanidin for PDE5A was assessed by molecular docking, molecular dynamics (MD) simulations, and microscale thermophoresis (MST) assay. The toxicity of procyanidin on penile corpus cavernosum smooth muscle (CCSM) cells (n=5) was evaluated. Additionally, its effects on intracellular cyclic guanosine monophosphate (cGMP) levels in CCSM cells (n=5) were evaluated. The absorption of procyanidin was evaluated by measuring plasma levels at various times after oral gavage to Sprague-Dawley (SD) rats (n=6). Subsequently, the effects of procyanidin on intracavernous pressure (ICP) and cGMP levels in penile cavernous tissue were evaluated in SD rats (n=6).Results: Procyanidin forms three hydrogen bonds with PDE5A and stabilizes the complex structure, exhibiting equilibrium dissociation constants (KD) value of 7.77 ± 2.39 μmol/L. Additionally, procyanidin exhibits minimal cytotoxicity toward CCSM cells and significantly elevates intracellular cGMP levels compared to the control group. In vivo studies demonstrate that procyanidin is rapidly absorbed, achieving peak blood concentrations within one hour. Simultaneously, procyanidin significantly increases ICP and cGMP levels in rats compared to the control group.Conclusion: These findings indicate that procyanidin sustains elevated cGMP levels within cells by targeting PDE5A, thereby exhibiting therapeutic efficacy in improving ICP. Procyanidin emerges as a promising PDE5I for treating ED and potentially other related conditions. Keywords: sexual dysfunctions, erectile dysfunction, cyclic guanosine monophosphate, microscale thermophoresis, cavernosum smooth muscle cells